Identifikasi Marka Polimorfik untuk Pemuliaan Padi Toleran Defisiensi Fosfor - Joko Prasetiyono; Hajrial Aswidinoor; Sugiono Moeljopawiro; Didy Sopandie; Masdiar Bustamam (Jurnal AgroBiogen, 2008)
Information on polymorphismsamong rice parents are very important in ricebreeding for tolerance to phosphorus defficiency. A studywas conducted at the Molecular Biology Laboratory,Indonesian Center Agricultural Biotechnology and GeneticResources (ICABIOGRAD) from October 2006 to July 2007 toidentify polymorphism markers from 6 rice genotypes. Therice genotypes, i.e., Dodokan, Situ Bagendit, Batur, Kasalath,NIL-C443, dan K36-5-1-1 were analyzed for polymorphismsusing 496 SSR markers, which cover the rice genomes.Seven of the 496 markers were used as foreground andrecombinant selection markers, and the rests (489 markers)were used as background selection markers. PCR amplificationswere separated on a 5% polyacrylamide gel andcolored by the silver staining method. Three different markersamong the seven foreground and recombinant selectionmarkers were selected from each crossing, which aretightly linked with Pup1 gene and have a distance less than 5cM. These markers are Dodokan vs Kasalath (RM277, SSR3,RM519), Dodokan vs NIL-C443 (RM277, SSR3, RM519),Dodokan vs K36-5-1-1 (RM277, SSR3, RM519), Situ Bagenditvs Kasalath (RM28102, SSR3, RM519), Situ Bagendit vs NILC443(RM28102, SSR3, RM519), Situ Bagendit vs K36-5-1-1(RM511, SSR3, RM519), Batur vs Kasalath (RM277, RM1261,RM519), Batur vs NIL-C443 (RM277, RM1261, RM519), andBatur vs K36-5-1-1 (RM28102, SSR3). Variations in backgroundselection primers were found in each chromosomeand in each parent combinations. Primers on chromosome4, 5, and 12 showed the lowest polymorphisms; moreprimers are needed for these chromosomes.